Inverse Analyses of Transport of Chlorinated Hydrocarbons Subject to Sequential Transformation Reactions - Casey, Francis X.M.; Šimůnek, Jiří (Journal of environmental quality, 2001)
ABSTRACT Chemical and biological transformations can significantly affect contaminant transport in the subsurface. To better understand such transformation reactions, an equilibrium–nonequilibrium sorption transport model, HYDRUS‐1D, was modified by including inverse solutions for multiple breakthrough curves resulting from the transport of solutes undergoing sequential transformations. The inverse solutions were applied to miscible‐displacement experiments involving dissolved concentrations of trichloroethylene (TCE) undergoing reduction and/or transformations in the presence of zero‐valent metal porous media (i.e., iron or copper‐coated iron filings) to produce ethylene. The inverse model solutions provided a reasonable description of the transport and transformation processes. Simultaneous fitting of multiple breakthrough curves of TCE and ethylene placed additional constraints on the inverse solution and improved the reliability of parameter estimates. Confidence intervals of optimized parameters were reduced significantly in comparison with those obtained by fitting TCE breakthrough curves independently. Further evidence for accurate parameter estimates was given when the parameter values agreed with previously reported values from independent batch and degradation experiments. Optimized values of the normalized degradation rates for the equilibrium (1.4 × 10−4 to 7.2 × 10−5 L h−1 m−2) and nonequilibrium (1.2 × 10−4 to 5.5 × 10−5 L h−1 m−2) models compared well with values (0.03 to 6.5 × 10−5 L h−1 m−2) obtained from previous studies. The estimated TCE–iron sorption coefficients (0.52 to 2.85 L kg−1) were also consistent with a previously reported value (1.47 L kg−1).